DOI: 10.11606/d.42.2014.tde-12082014-155111
|View full text |Cite
|
Sign up to set email alerts
|

Ação do imunomodulador P-MAPA sobre o sistema complemento e receptores do tipo Toll em modelo de inflamação induzida por lipopolissacarídeo.

Abstract: Título da Dissertação: Ação do imunomodulador P-MAPA sobre o sistema complemento e receptores do tipo Toll em modelo de inflamação induzida por lipopolissacarídeo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In agreement with our findings, trials using the same experimental model were carried out with formulations containing curcumin, and their retention in the skin was prolonged. The authors suggested a potential use of curcumin in antiaging formulations due to this property 28 …”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, trials using the same experimental model were carried out with formulations containing curcumin, and their retention in the skin was prolonged. The authors suggested a potential use of curcumin in antiaging formulations due to this property 28 …”
Section: Discussionmentioning
confidence: 99%